2015
DOI: 10.3892/ol.2015.3679
|View full text |Cite
|
Sign up to set email alerts
|

Endostar enhances the antitumor effects of radiation by affecting energy metabolism and alleviating the tumor microenvironment in a Lewis lung carcinoma mouse model

Abstract: Abstract. Lung cancer is a leading cause of morbidity and mortality. Previous studies have identified that an improvement in treatment efficacy was achieved using Endostar; however, the role of Endostar in lung cancer remains poorly understood. The present study investigated whether the enhanced antitumor effects of Endostar in combination with radiation involved changes in the metabolism and microenvironment in non-small cell lung cancer. A Lewis lung carcinoma mouse model was used, including the control, End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Tumor volumes were calculated according to the formula V = a × b 2 × 0.5, where a was the longest diameter and b was the maximum transverse diameter. The tumor volumes were measured up to 17 days with a vernier caliper, and then the mice were sacrificed, and tumors from each group were surgically excised, rinsed with PBS, wiped, weighed, and photographed (Meng et al., 2013 ; Zheng et al., 2015 ; Zhu et al., 2015 ; Tang et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tumor volumes were calculated according to the formula V = a × b 2 × 0.5, where a was the longest diameter and b was the maximum transverse diameter. The tumor volumes were measured up to 17 days with a vernier caliper, and then the mice were sacrificed, and tumors from each group were surgically excised, rinsed with PBS, wiped, weighed, and photographed (Meng et al., 2013 ; Zheng et al., 2015 ; Zhu et al., 2015 ; Tang et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, previous study revealed that Endostar was involved in the regulation of both metabolism and tumor microenvironment hypoxia, which may be responsible for enhanced antitumor effects of Endostar combined with radiotherapy (43). For inoperable locally advanced NSCLC, further exploration and research into whether the addition of Endostar on the basis of the new standard of CCRT plus consolidation immunotherapy can further improve the therapeutic effects and also play a role in radiological protection is warranted.…”
Section: Survival Analysismentioning
confidence: 99%
“…Another hypoxia modifier, Endostar (recombinant human endostatin), is a novel artificially synthesized anti-angiogenic agent that has been approved for clinical use. Endostar has been found to enhance the anti-tumor effects of radiation therapy by altering the tumor’s energy metabolism and micro-environment through hypoxia modification, as demonstrated in murine models 89. The addition of Endostar to chemo-radiation therapy is being evaluated in both a phase II study of patients with postoperative high-risk early-stage cervical cancer (NCT03622827, Table 3) and a multi-institutional phase III study of women with cervical cancer (FIGO (2009) stage Ib, IIa2, IIb–IVa) (NCT03086681, Table 3).…”
Section: Cellular Pathway Inhibitors and Other Agents: Signaling Gromentioning
confidence: 99%